EVALUASI KEBIJAKAN PEMERINTAH DALAM MENJAGA STABILITAS PERTUMBUHAN EKONOMI TAHUN 2013 - Ahmad Azmy (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2014)
This study aimed to evaluate government policies through several fiscal and monetary stimulus in stabilizing economic growth through interest rate policy, the money supply and inflation in Indonesia during 2013. The variables used were the BI rate, the money supply (M2), and inflation. This study using Pearson correlation analysis to measure the relationship between these three variables. The results of this study indicate that the BI rate has a significant positive correlation to the amount of money supply (M2). BI rate has no significant negative correlation to inflation. While the money supply has no significant positive correlation to inflation (M2). These anomalies can be caused by fluctuation of currency exchange rates on foreign currency Indonesia, balance of payments, current account deficit, or the amount of government debt that is maturing. For the case of Indonesia, the policy to control inflation through interest rate increases become ineffective if some basic assumptions both Keynesian and Monetarist not met.DOI: 10.15408/sjie.v3i1.2064